Randomised controlled trial of efficacy of teaching patients with bipolar disorder to identify early symptoms of relapse and obtain treatment. Issue 7177 (16th January 1999) - Perry, Alison; Tarrier, Nicholas; Morriss, Richard; McCarthy, Eilis; Limb, Kate
Abstract: Objective: To determine the efficacy of teaching patients with bipolar disorder (manic-depressive psychosis) to identify early symptoms of relapse and seek prompt treatment from health services. Design: Single blind randomised controlled trial with matching on four baseline variables using a minimisation algorithm. Setting: Mental health services in four NHS trusts (one teaching, three non-teaching). Subjects: 69 patients with bipolar disorder who had had a relapse in the previous 12 months. Interventions: Seven to 12individual treatment sessions from a research psychologist plus routine care or routine care alone. Main outcome measures: Time to first manic or depressive relapse, number of manic or depressive relapses, and social functioning examined by standardised interviews every six months for 18 months. Results: 25th centile time to first manic relapse in experimental group was 65weeks compared with 17weeks in the control group. Event curves of time to first manic relapse significantly differed between experimental and control groups (log rank 7.04, df=1, P=0.008), with significant reductions in the number of manic relapses over 18months (median difference 30% (95% confidence interval 8% to 52%), P=0.013). The experimental treatment had no effect on time to first relapse or number of relapses with depression, but it significantly improved overall social functioning (mean difference 2.0(0.7to 3.2), P=0.003) and employment (mean difference 0.7(0.1to 1.3), P=0.030) by 18months. Conclusion: Teaching patients to recognise early symptoms of manic relapse and seek early treatment is associated with important clinical improvements in time to first manic relapse, social functioning, and employment.